2016
DOI: 10.1016/j.semarthrit.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of cutaneous manifestations in late- versus early-onset systemic lupus erythematosus

Abstract: Objectives Although systemic lupus erythematosus (SLE) most commonly occurs in reproductive-age women, some are diagnosed after age 50. Recognizing that greater than one third of SLE criteria are cutaneous, we undertook a systematic review and meta-analysis to evaluate differences in cutaneous manifestations in early and late-onset SLE patients. Methods We searched the literature using PubMed, CINAHL, Web of Science and Cochrane Library. We excluded studies that did not include ACR SLE classification criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 37 publications
2
27
0
3
Order By: Relevance
“…Although not always consistent across studies, patients with childhood‐onset SLE tend to have a more severe and aggressive disease, whereas patients with late‐onset SLE show a more indolent and less severe clinical course than those with adult‐onset SLE . In our cohort, renal involvement was more frequent in patients with childhood‐onset SLE, whereas typical cutaneous presentations, such as malar rash, were less common in patients with late‐onset SLE, which is similar to findings of previous reports . Both childhood‐onset and late‐onset SLE were associated with higher mortality than adult‐onset SLE in the present study (Table ), and this finding is in line with those of previous studies .…”
Section: Discussionsupporting
confidence: 84%
“…Although not always consistent across studies, patients with childhood‐onset SLE tend to have a more severe and aggressive disease, whereas patients with late‐onset SLE show a more indolent and less severe clinical course than those with adult‐onset SLE . In our cohort, renal involvement was more frequent in patients with childhood‐onset SLE, whereas typical cutaneous presentations, such as malar rash, were less common in patients with late‐onset SLE, which is similar to findings of previous reports . Both childhood‐onset and late‐onset SLE were associated with higher mortality than adult‐onset SLE in the present study (Table ), and this finding is in line with those of previous studies .…”
Section: Discussionsupporting
confidence: 84%
“…These data agree with those of the literature as SLE is most common in patients below 50 years. 35 Particularly, early-SLE (age <50 years) seems to have cutaneous manifestations more often than late-SLE (age > 50 years). These differences seem to be associated with many factors including age, immunosenescence, environment and immunogenetics.…”
Section: Discussionmentioning
confidence: 98%
“…[6] However, data literature within the late-onset group is conflicting. A very recent systematic review and metaanalysis done by Medlin et al [7] found that, while cutaneous signs are still common, they are less common compared to early-onset SLE with malar rash, photosensitivity and alopecia occurring less frequently and sicca symptoms being more common among the elderly group. This differed in our patient, in which the photosensitive rash helped us to clinch the diagnosis.…”
Section: Sle Is An Autoimmune Disorder With Variable Clinical and Immmentioning
confidence: 99%